Uses and benefits of digital sequence information from plant genetic resources: Lessons learnt from botanical collections. Issue 1 (21st September 2021) - Cowell, Carly; Paton, Alan; Borrell, James S.; Williams, China; Wilkin, Paul; Antonelli, Alexandre; Baker, William J.; Buggs, Richard; Fay, Michael F.; Gargiulo, Roberta; Grace, Olwen M.; Kuhnhäuser, Benedikt G.; et al.
Abstract : Societal Impact Statement: Digitized molecular data are vital to numerous aspects of scientific research and genetic resource use. The Convention on Biological Diversity currently refers to this as "Digital Sequence Information" (DSI), a term not widely adopted by science and lacking a clear definition. There are concerns over the access to genetic resources and absence of benefit sharing by provider countries. Open access to DSI might exacerbate this, which is leading to increasing policy interventions and restricted access to genetic resources and DSI. We analyze current international debate and proposed solutions and provide case studies of DSI use producing tangible benefits for the provider countries and scientific research, demonstrating the importance of open access DSI to achieving conservation goals. Summary: Substantial advances in DNA sequencing over the last decades hold great potential to enhance food security and sustainable use of global biodiversity, benefiting the world's poorest people. Digital Sequence Information (DSI) plays a crucial role in catalyzing research applications that can contribute to international societal and biodiversity conservation targets. However, benefit sharing relating to DSI is difficult to identify and hindered by the lack of clear international governance and legislation, which in turn has led to a reluctance to make DSI publicly and freely available. Critically, no precise definition exists under the Convention on Biological Diversity (CBD), the Nagoya Protocol (NP), or the International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA). The key difference between DSI and biological resources, for which access and use are highly regulated under those frameworks, is that information is nonphysical. Information can be replicated and used without movement of, or access to, physical specimens. Thus, regulating the use of DSI is extremely challenging and remains controversial. Here, we review the regulation of DSI and the possible future steps by the international community, in the context of the benefit‐sharing obligations of the CBD, NP, and ITPGRFA. We highlight how multilateral agreements work in practice and are a solution to this impasse. We provide case studies demonstrating how the Royal Botanic Gardens, Kew, and its collaborators address the uncertainty surrounding the use of DSI, illustrating tangible and equitable benefits that have arisen from such use. We conclude that open access to DSI is needed for scientific research and international policy. Abstract : Digitized molecular data are vital to numerous aspects of scientific research and genetic resource use. The Convention on Biological Diversity currently refers to this as "Digital Sequence Information" (DSI), a term not widely adopted by science and lacking a clear definition. There are concerns over the access to genetic resources and absence of benefit sharing by provider countries. Open access to DSI might exacerbate this, which is leading to increasing policy interventions and restricted access to genetic resources and DSI. We analyze current international debate and proposed solutions and provide case studies of DSI use producing tangible benefits for the provider countries and scientific research, demonstrating the importance of open access DSI to achieving conservation goals.